Female leaders in the 21st century in a masculine world/Vroulike leiers in die 21ste eeu in 'n manlike wereld - Kessler, Ma (Koers (Potchefstroom, South Africa), 2014)
The 21st century shows an increase in the number of women occupying leadership positions. The challenge is: How do they lead in a context which is still male dominated? Often female leaders simply try to copy the male leadership style they are familiar with. But sometimes, in doing so, they lose their femininity and the organisation misses out on the specific opportunities of female leadership. One aim of this article is to discuss the opportunities and strengths of a female leadership style such as pro-social behaviour and a panorama view. We will also deal with the issue of how women approach power and the power bases women would typically use. One conclusion is that we need the benefits of both male and female leadership for the 21st century. Die 21ste eeu toon 'n toename in die aantal vroue in leierskapsposisies. Die uitdaging is: Hoe kan hulle lei in 'n konteks wat steeds deur mans oorheers word? Dikwels probeer vroulike leiers eenvoudig die manlike leierskapstyl waarmee hulle vertroud is, naboots. As 'n gevolg verloor vroue soms hul vroulikheid en organisasies verloor die spesifieke geleenthede wat vroulike leierskap bied. Een doel van hierdie artikel is om die geleenthede en sterkpunte van 'n vroulike leierskapstyl, soos pro-sosiale gedrag en 'n panorama-uitsig, te bespreek. Ons sal ook kyk na die kwessie van vroue se benadering tot mag en die magsbasisse wat vroue tipies gebruik. Een gevolgtrekking is dat ons die voordele van beide manlike en vroulike leierskap vir die 21ste eeu benodig.